Impact of sales promotion on customer intention to purchase high involvement product / Teck-Weng Jee - Jee, Teck-Weng (Universiti Teknologi MARA Cawangan Sarawak, 2018)
Sales promotion is a very common targeting strategy used by retailers, yet personal value and sales promotion technique preferences that contribute towards customer satisfaction and intention to purchase high involvement product are largely unknown. This study adopted pseudo-experimental factorial design, with the aim of examining the difference in purchase satisfaction and behavioral intention between consumers’ different personal value and sales promotion techniques preferences for high involvement product from retailing service perspective. The findings from this study expand current knowledge on similar areas of sales promotion where this study details the variance effect of personal value and sales promotion techniques preferences on purchase satisfaction and behavioral intention. The study suggests to practitioners that it is crucial to understand the impact of personal value and sales promotion techniques preferences, particularly when selecting appropriate strategies for better market segmentation and targeting for high involvement product